Perancangan User Experience Pembelajaran Digital Marketing berbasis Mobile menggunakan Metode Design Thinking - Bagas Noor Rachman; Herman Tolle; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Technological advances must be balanced with their human resources, to achieve that humans need an adaptation and learning. As is the case according to data from the Malang city government, micro, small and medium enterprises (UMKM) in Malang are still on a microscale and the development every year is not so rapid. It needs a supporting tool for UMKM actors in learning and understanding technology in managing their business, one of which is learning about Digital Marketing. The design of this interaction design uses desgin thinking method that focuses on what the user really needs, by going through several stages namely understanding and determining the system user, analyzing system needs, creating solution design and testing the design of the system. In the Usability test was conducted to 20 participants with Remote Usability Testing Technique and used system usability scale (SUS) questionnaire, then obtained test results that are effectiveness aspect by 99% then on efficiency aspect get a score of 98% and Satisfaction value 76,125 which means to get Grade B, with the results of the score obtained by the system design including to the category 'Good'.